Hepatocellular Carcinoma in Nonalcoholic Steatohepatitis - Arshad, Hafiz Muhammad Sharjeel; Koppe, Sean (Digestive Disease Interventions, 2017)
Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of chronic liver disease in the United States. Approximately 10 to 20% of patients with NAFLD progress to nonalcoholic steatohepatitis (NASH). NASH can progress to cirrhosis, which, in turn, can lead to hepatocellular carcinoma (HCC). However, evidence also supports that HCC can develop in patients with NASH who do not have cirrhosis or advanced fibrosis. Obesity, diabetes mellitus, hepatic iron deposition, and insulin resistance are potential risk factors for HCC in NASH. Mechanisms proposed include a role for tumor necrosis factor-α, interleukin-6, insulinlike growth factor, and nuclear factor κβ activation in progression of NASH to HCC. Polymorphisms in patatin-like phospholipase domain-containing 3 also support a genetic influence in NASH-related HCC. Surgical resection, liver directed therapy, and liver transplant remain the mainstay of therapy. Ultrasound has reduced sensitivity for surveillance of HCC in obese patients and alpha fetoprotein may have more value for HCC surveillance in the NASH patient as compared with the HCV patient. Although HCC can develop in noncirrhotic NASH, currently there are no guidelines to recommend surveillance in noncirrhotic NASH patients.
Keywords: nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; fatty liver disease; hepatocellular carcinoma